SOSIALISASI MENGANAI DAMPAK BANGUNAN PANTAI TERHADAP ABRASI DI PESISIR BARAT PANTAI PANGANDARAN - Yuyun Hidayat; Hazman Hiwari; Subiyanto Subiyanto (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The coastal area is one area that has complex dynamics. One phenomenon that is known to have an impact on coastal activities is the erosion of the coastal area called Abrasion.  Integrated KKNM-PPM  is a community service activity of Padjadjaran University, which is carried out annually in several regions. The program can be used as a distribution of knowledge as well as community service at Padjadjaran University students, in this case, providing education about this abrasion phenomenon. The location for the integrated KKNM is RT 01 RW 04 Bojongsalawe Hamlet, Karangjaladri Village, Parigi District, Pangandaran Regency. We have known that the coastal areas in the Karangjaladri Coast area are areas that occur annually with abrasion phenomena, ranging from 0.01 to 1.2 ha erosion in a year. The Information of this paper, it is expected that the region can wisely use the process.